Menelaah Imaji Dan Struktur Batin Dalam Puisi “HUJAN” Karya Achluddin Ibnu Rochman Menggunakan Pendekatan Struktural - Puja Sri Rahayu; Salwa Rachmadini (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2025)
This research aims to examine images and inner structures using a structural approach in the poem Rain by Achluddin Ibnu Rochman. The author chooses the images and inner structure in the poem Rain as the object of poetry that will be studied structurally. The formulation of the problem in this research is what the inner structure is in the images of Rain poetry. The method in this research uses a structural approach which aims to reveal and describe the inner structure contained in the poetic images. Based on the results of this research, the analysis of the poem contains a romance theme and has a melancholic feeling or atmosphere because of the sincerity of love and has a tone that tends to be turbulent and suppressed emotions and has a moral message or mandate so that every reader has the character of trust, patience, steadfastness and sensitivity.